2022
DOI: 10.1186/s12931-022-01995-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary 99mTc-HMDP uptake correlates with restrictive ventilatory defects and abnormal lung reactance in transthyretin cardiac amyloidosis patients

Abstract: Background Pulmonary involvement in individuals with transthyretin cardiac amyloidosis is unclear. The aim of this study was to quantify 99mTc-hydroxy methylene diphosphonate (HMDP) lung retention in hereditary transthyretin (ATTRv) cardiac amyloidosis patients and to relate tracer uptake intensity to pulmonary function and aerobic capacity. Methods We prospectively enrolled 20 patients with biopsy-proven ATTRv cardiac amyloidosis and 20 control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Extra-cardiac uptake was found predominantly in the lungs and pleura in ATTR and in AL, followed by the digestive track and subcutaneous tissues in hereditary ATTR and AL cardiac amyloidosis. Another study by Monfort et al, 18 specifically looked at lung retention in hereditary ATTR, showing that pulmonary retention of HMDP was higher in hereditary ATTR amyloidosis patients compared with age and sex matched control subjects. Another study from Cappelli et al 19 found 99m Tc-HMDP scintigraphy showed lung uptake in almost 60% of subjects with ATTR amyloidosis, and that the incidence of lung uptake was significantly correlated to the grade of heart retention according to Perugini visual score.…”
Section: Step 1 Visual Interpretationmentioning
confidence: 99%
“…Extra-cardiac uptake was found predominantly in the lungs and pleura in ATTR and in AL, followed by the digestive track and subcutaneous tissues in hereditary ATTR and AL cardiac amyloidosis. Another study by Monfort et al, 18 specifically looked at lung retention in hereditary ATTR, showing that pulmonary retention of HMDP was higher in hereditary ATTR amyloidosis patients compared with age and sex matched control subjects. Another study from Cappelli et al 19 found 99m Tc-HMDP scintigraphy showed lung uptake in almost 60% of subjects with ATTR amyloidosis, and that the incidence of lung uptake was significantly correlated to the grade of heart retention according to Perugini visual score.…”
Section: Step 1 Visual Interpretationmentioning
confidence: 99%